Honoring Team Decision-Making During Manifestation Determination Meetings Through Collaborative and Proactive Solutions. (January 2022) - Trapp, Laura; Gershwin, Tracy; Robinson, Jason
The Individuals With Disabilities Education Act requires schools to conduct a manifestation determination (MD) meeting when suspending students with disabilities for more than 10 days. The MD procedure is intended to safeguard educational access by providing a process to determine if a student's disability is related to the suspending behavior. An accurate decision requires educational team members to effectively collaborate to review relevant data and the student's Individualized Education Program. Collaborative and proactive solutions (CPS) offer a framework for collaboration that may ensure that all team members meaningfully participate during the MD meeting while encouraging a rigorous analysis of student-specific data. The use of CPS is proposed as a framework to generate meaningful collaboration in MD meetings, which may result in positive student outcomes that reach beyond merely addressing a behavioral violation.